Peran Pemerintah Daerah Jawa Barat dalam Upaya Pemenuhan Hak Pedagang Tradisional melalui Revitalisasi Pasar Perkotaan - Yuliana Primawardani (Badan Strategi Kebijakan Hukum, 2014)
The traditional market is one of the driving joints for society Indonesian economy . In this case the market becomes a meeting place sellers and buyers to trade in order to meet daily needs . However , in line with the changing times , the existence of traditional markets as if marginalized . This is because market conditions traditionally considered less worthy as areea trade , so that the traditional merchant was unable to compete with modern markets such as supermarkets and hypermarkets that exist today . This happens in various provinces, including the province of West Java which has increased the number of retail businesses in each county / city . Therefore it is necessary to assist the Government's attention in the traditional traders obtain their rights through the development and rejuvenation of urban markets in order to compete with the modern retail business as stipulated in Presidential Regulation of the Republic of Indonesia Number 112 of 2007 on Management and Development of Traditional Markets , Shopping and Modern Stores .